Grafting of hydroxymethylacrylamide and acrylic acid copolymer onto polyvinylidene fluoride membrane by supercritical carbon dioxide and its application in dye separation. (1st April 2014) - Hou, Minna; Cao, Liqin; Wang, Jide; Lin, Jiangli; Zhao, Mengqi; Wang, Gang
<x xml:space="preserve">Abstract</x> We report a thermally induced graft copolymerization of acrylic acid and N‐hydroxymethylacrylamide onto polyvinylidene fluoride microporous membrane by using supercritical carbon dioxide as a solvent and carrier agent. The effects of monomer mole ratio, pressure, reaction temperature, time, and initiator concentration on the degree of grafting were investigated. The morphology of the grafted membrane was studied via scanning electron microscopy. Attenuated total reflectance infrared spectroscopy spectroscopy and X‐ray diffraction proved the existence of grafting monomers. The results of contact angle measurement and water filtration at different pH levels indicated pronounced pH‐sensitive behavior and increased hydrophilicity of the polyvinylidene fluoride grafted membrane. In particular, the grafted membrane was applied to the removal of methylene blue with a relative rejection of 98.1% compared with 30.5% of rejection observed from the pristine polyvinylidene fluoride membrane. Copyright © 2014 John Wiley & Sons, Ltd.